Clinical, Radiographic and Histological Evaluation of the Plastic Spiked Washer in the Dog - Boudrieau, R. J.; Schelling, S. H.; Tidwell, A. S. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Plastic spiked washers and metal washers were implanted in the periarticular soft tissues of six joints in three experimental dogs. These dogs were followed clinically and radiographically over a 16 week time frame, at which time they were euthanatized and histological evaluation was obtained. Differences were not observed clinically nor radiographically between joints, nor between locations, with the different implant devices throughout the time frame investigated in the experimental dogs. Histological evaluation revealed a very minimal to mild, fundamentally identical inflammatory response to all of the implants in all of the specimens; however, in three specimens (plastic spiked washers), very infrequent lesions of a few randomly scattered microgranulomas, surrounded by a fibrous connective tissue envelope, were observed. The histological response of a limited inflammatory reaction was comparable to the positive controls using metal washers in the experimental dogs, despite the few microgranulomas observed. A clinical retrospective evaluation of 31 joints in 29 dogs from 1992 to 1996, in which a plastic spiked washer was implanted, also was performed. Long term follow up (mean 2.6 years) of 21 dogs in the clinical case series revealed no complications related to infection or a foreign-body reaction. Both the experimental and clinical studies supported the authors’ impression that the plastic spiked washer is well tolerated over the long term.A 16 week experimental study was performed in three dogs (six joints) in order to evaluate if any clinical, radiographic or histological differences could be found in the periarticular soft tissues with implantation of either a plastic spiked washer or a metal washer. No differences were observed clinically or radiographically between joints, or between locations, with the different implants. Histological evaluation revealed a very minimal to mild inflammatory response to all of the implants; however, a few very infrequent and randomly scattered microgranulomas were observed in response to the plastic spiked washers.
Keywords: Plastic spiked washer; inflammation; foreign-body microgranuloma